The perception of product quality and the intention to repurchase on shirt/blouse products made in China amongst consumers in Kota Kinabalu - Sun Yu (2015)
The purpose of this study is to examine the relationship between product quality concerned in the eight quality dimensions and the intention to repurchase on shirt/blouse products made in China in Kata Kinabalu, Sabah. The study has conceptualized that product quality as a multidimensional construct which consists of eight dimensions, which are performance, features, reliability, conformance, durability, aesthetics, serviceability and perceived quality, and an uni-dimensional construct, the intention to repurchase. There were 229 respondents used for the statistic analysis. The data was gathered using survey interview questionnaire through snowballing technique in Kata Kinabalu. From the framework of this study, eight hypotheses have been developed and tested using PLS-SEM. The result showed that product performance, features, reliability, aesthetics and perceived quality positively impact on consumers' repurchase intentions on the shirt/blouse products made in China. The finding of this research suggested that performance, features, reliability, aesthetics and perceived quality are essential for China export companies because that directly influence consumers' repurchase behavior. Future research should do a similar study in light of the relationship between eight quality dimensions and the intention to repurchase on other products made in China, such as electronics or electronic products in other states of Malaysia.